Updated distribution and conservation assessment of Darcyanthus spruceanus, Deprea cardenasiana and Deprea ecuatoriana (Solanaceae): new reports for Peru and Brazil - Cueva Manchego, Marco A.; Grich, Agustina; Deanna, Rocío (Phytotaxa, 2020)
Darcyanthus and Deprea are neotropical nightshade genera with Andean distributions in South America. Here we present an updated distribution and conservation assessment of Darcyanthus spruceanus, Deprea cardenasiana and D. ecuatoriana, including the first report of D. cardenasiana in southern Peru and the monotypic Darcyanthus in western Brazil. In addition, D. ecuatoriana distribution in northern Peru is confirmed after new revision of herbarium material. Deprea cardenasiana occurs in the southern limit of the genus distribution and it had not been recollected after its discovery almost 79 years ago. Deprea ecuatoriana is currently restricted to the montane forests from northern Peru and southern Ecuador. The monotypic Darcyanthus reaches lowland areas, including Amazonian forest in Peru, Bolivia and Brazil. According to IUCN criteria, both D. cardenasiana and D. ecuatoriana are categorized as Endangered whereas Darcyanthus spruceanus is considered as a Least Concern species.